Mobile health applications for older people in Asia: protocol for a systematic review of end-user perceptions and recommendations - Yvonne Wong; Lorna Kwai Ping Suen; Yijian Yang; Simon Ching Lam; Kim Wai Raymond Sum; Wilson Leung; Ching Lam Chan; Janice Ngar Lam Chow; Jasmine Cheung; Edward Shum; Agnes Wing Ki Yip; Winsy Wing Yu Wan; et al. (BMJ Open)
Introduction Mobile technology has revolutionised the way people interact with others and gain access to healthcare services. Given that cultural background is a strong moderator for technology penetration, this systematic review aims to examine end-user perceptions and design recommendations for mobile health applications among Asian older people.Methods and analysis Five electronic databases (PubMed, CINAHL, PsycINFO, Medline and Cochrane Central Register of Controlled Trials) will be searched until May 2025. Studies conducted on Asian older people aged 60+ years, with English/Chinese full text available, will be included. Narrative approaches and effect direction plots will be used for data analyses. Risk of bias across studies will be examined using Cochrane Risk of Bias 2 and Risk of Bias in Nonrandomised Studies of Interventions, whereas the quality of evidence will be assessed by Shekelle’s classification scheme.Ethics and dissemination No ethical approval will be required. The findings will be disseminated through peer-reviewed journal articles.PROSPERO registration number CRD42024562861.